1998
DOI: 10.1177/002234099805200403
|View full text |Cite
|
Sign up to set email alerts
|

Including the Ultimate: A Spiritual Focus Treatment Program in an Inpatient Psychiatric Area of a Hospital in Partnership with a Pastoral Counseling Center

Abstract: Describes how an American Association of Pastoral Counselor (AAPC) accredited pastoral counseling center and a community medical center developed in inpatient psychiatric treatment program which integrated the spiritual/religious resources of patients. Outlines the process of collaboration, some basic principles of the integration of faith resources, the ways that staff resistance surfaced and substantially was overcome, and the positive responses of patients. Notes the decision to base treatment on the religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…With regard to patients with acute religious delusions, although some of the literature cautions against PaC providers interacting directly with patients with acute religious delusions, finding it ineffective 17 or excluding this population from studies, 34,35 other publications suggested potential benefits of having PaC providers involved with this population, such as providing context as to whether or not a belief is appropriate or delusional. 2,41 Although articles on spiritual healing did not deal with PaC providers and were therefore not included in our review, 1 article describing a study of elderly Egyptian patients with schizophrenia suggested that spiritual healing could be associated with an increased risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With regard to patients with acute religious delusions, although some of the literature cautions against PaC providers interacting directly with patients with acute religious delusions, finding it ineffective 17 or excluding this population from studies, 34,35 other publications suggested potential benefits of having PaC providers involved with this population, such as providing context as to whether or not a belief is appropriate or delusional. 2,41 Although articles on spiritual healing did not deal with PaC providers and were therefore not included in our review, 1 article describing a study of elderly Egyptian patients with schizophrenia suggested that spiritual healing could be associated with an increased risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,22,33 Second, the authors reported feeling most effective as PaC providers when they are integrated into the care team 13,26 and given definitive roles that are made clear to other team members. 13,18 Six nonevaluative reports described PaC integration models and detailed how a PaC provider functions when integrated into inpatient psychiatric care team and discussed the attitudes of 24 Rattray 29 Stephens 31 Jensen et al 35 patients and staff members toward the PaC provider in this role. These articles fall into 2 categories: (1) descriptions of specific spirituality groups/ worship services run by a PaC provider and (2) descriptions of patient and staff perceptions of the PaC provider.…”
Section: Nonevaluative Reportsmentioning
confidence: 99%
See 3 more Smart Citations